1995
DOI: 10.1007/bf02347655
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of leaf carbon gain in saplings of Thujopsis dolabrata var. hondai and Quercus mongolica var. grosseserrata in a cool‐temperate deciduous forest

Abstract: Seasonal courses of leaf CO 2 gas exchange in a growing season were examined in saplings of Thujopsis dolabrata'var, hondai and Quercus mongolica var. grosseserrata in a cool temperate deciduous forest. Between the two tree species there were no large differences in the light compensation point of leaf photosynthesis, except for the season of new leaf expansion. However, light-saturated rates of net photosynthesis were obviously high in T. dolabrata var. hondai. Evergreen T. dolabrata var. hondai saplings had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…These different levels of photosynthesis in different seasons suggest that the phenology of canopy trees has a great effect on the seasonal pattern of photosynthesis by understory hiba seedlings. Similar seasonal patterns are also seen in hiba (Hashimoto and Shirahata 1995) and other understory species (Taylor and Pearcy 1976;Walters and Reich 1999;Rothstein and Zak 2001;Katahata et al 2005). Further, it should be possible to predict the growth of hiba seedlings in mixed forests by taking into account the length of foliation period of canopy trees.…”
Section: Leaf Characteristics and Their Plasticity With Respect To LIsupporting
confidence: 71%
See 1 more Smart Citation
“…These different levels of photosynthesis in different seasons suggest that the phenology of canopy trees has a great effect on the seasonal pattern of photosynthesis by understory hiba seedlings. Similar seasonal patterns are also seen in hiba (Hashimoto and Shirahata 1995) and other understory species (Taylor and Pearcy 1976;Walters and Reich 1999;Rothstein and Zak 2001;Katahata et al 2005). Further, it should be possible to predict the growth of hiba seedlings in mixed forests by taking into account the length of foliation period of canopy trees.…”
Section: Leaf Characteristics and Their Plasticity With Respect To LIsupporting
confidence: 71%
“…For instance, light resource for growth and survival of plants under shade of deciduous trees depend on the phenological gap made by the canopy trees (Taylor and Pearcy 1976;Rothstein and Zak 2001). Similarly, Hashimoto and Shirahata (1995) reported that hiba seedlings under a canopy of oak trees achieved positive photosynthetic production in only two short periods per year: before the oak foliage emerged in the spring, and after leaf fall in the autumn, which was a critical factor in the survival of the hiba seedlings. Thus, the leaf expansion period of overstory trees may strongly affect the photosynthetic production and survival of hiba seedlings in mixed forests.…”
Section: Introductionmentioning
confidence: 94%
“…They probably occurred because in these conditions the seedlings could not add further resources to their reserves (cf. Hashimoto and Shirahata 1995) and, instead, consumed reserves in order to survive. In such cases carbohydrate storage would decline as the seedlings aged.…”
Section: The Effect Of Ambient Light Conditions On the Level Of Carbomentioning
confidence: 98%
“…Its seedlings are highly shade tolerant (Hashimoto and Shirahata 1995), and it generally grows slowly during such an early growth stage (Takahashi 1937;Itoya 1987Itoya , 1988Tanabe and Onodera 1996). However, the growth rate of T. dolabrata increases rapidly in response to improvements in the local light environment at both seedling (Ota et al 2004) and adult stages (Shimizu 1937;Sakurai et al 1986;Sugita 1993a, b).…”
Section: Introductionmentioning
confidence: 95%